PENGARUH LITERASI KEUANGAN, MODAL USAHA DAN INOVASI TERHADAP KINERJA KEUANGAN UMKM SEKTOR PERDAGANGAN DI KECAMATAN SUKASADA - Maharani, Ni Putu Gita Sari; Dewi, Gst. Ayu Ketut Rencana Sari; Atmaja, I Made Dwita (Universitas Pendidikan Ganesha, 2025)
This research was conducted on MSMEs in the trade sector in Sukasada District. The purpose of this study is to examine the effect of financial literacy, business capital, and innovation on the financial performance of MSMEs in the trade sector in Sukasada District. The population in this study consists of 93 MSME actors in Sukasada District. The sample was determined using a purposive sampling technique, with a total of 63 respondents. Data collection was carried out using a questionnaire with a Likert scale. The research design used is a quantitative causal approach. The data analysis techniques employed include multiple linear regression analysis, hypothesis testing (t-test), and the coefficient of determination. Data processing was performed using SPSS software version 25. The results show that: (1) financial literacy has a positive and significant effect on the financial performance of MSMEs; (2) business capital has a positive and significant effect on the financial performance of MSMEs; and (3) innovation has a positive but not significant effect on the financial performance of MSMEs in Sukasada District.